RELEVANSI ETIKA ARISTOTELES DENGAN ETIKA PANCASILA - Suyahmo, - (Faculty of Social Science, Universitas Negeri Semarang, 2009)
Especial Target of ethics Aristoteles is orient at public bliss. Bliss like this in line with especialÃ‚Â target of ethics is in the form of Ã¢â‚¬Å“or especial moralÃ¢â‚¬Â, that is especial and intellectual especial of moral.Ã‚Â Intellectual especial pass the theoretical wisdom is whch only can be conducted by intellectual circle;Ã‚Â while especial of moral pass the practical wisdom is which in this case human being have to able toÃ‚Â determine the a middle course to two both of the same deed of ekstrem throw to interfere in and able toÃ‚Â run the activity by following objective kindliness standart which is by public thought well of. AccordingÃ‚Â to Aristoteles of so that human being reach the high bliss with quality as refection dream of the idealÃ‚Â life, hence human being have to able to look into the truth. In this case anly a steel philosopher capableÃ‚Â to reach it and axecute it. That ethics Aristoteles is relevant its contents payload and in line with ethicsÃ‚Â Pancasila, what is two placing Ã‚Â forward wisdom by taking one thing with another, as manifestasi senseÃ‚Â of justice, moderation, and impregnability.Keywords : ethics Aristoteles, ethics Pancasila